Description of the second species of Polletomyia Curler, 2020 (Diptera: Psychodidae) from the Brazilian Amazon - Bravo, Freddy; Araújo, Maíra Xavier (EntomoBrasilis, 2023)
Polletomyia Curler, 2020 is a Neotropical genus of Psychodidae that was established based on Polletomyia subulata Curler, 2020 from French Guiana. In this paper, we describe a second species of the genus from the Brazilian Amazon. The specimens were collected by the late Larry Quate, a psychodid expert, and are deposited at the Museu de Zoologia of Universidade Estadual de Feira de Santana. We provide illustrations and descriptions of both males and females of the new species.